The Impact of Firm Size, Capital Intensity Ratio, Inventory Intensity Ratio and Leverage Toward Effective Tax Rate on Consumer Goods Companies Listed on the Indonesia Stock Exchange - Lu, Jeniefer; Dananjaya, Yanuar (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Effective Tax Rate is an indicator of tax management as measured by comparing tax burden to pre-tax income. The effective tax rate is used to measure the amount of tax that is borne by the company against the company's accounting profit, so the company can know the performance of its tax management. The objective of this research is to analyze the impact of firm size, capital intensity, inventory intensity, and leverage toward effective tax rate in consumer goods companies listed on Indonesia Stock Exchange (IDX) during the period 2018-2021. The population of this research is the state-owned enterprises listed on Indonesia Stock Exchange during 2018-2021. Further, with the employed purposive sampling and determined criteria, 32 companies are chosen as the samples. The data analysis method applied is multiple linear regression which is processed through SPSS 26th version. The result of this research shows that firm size, capital intensity have no impact toward effective tax rate. However, inventory intensity has an insignificant positive impact toward effective tax rate. Furthermore, leverage has a significant positive impact toward effective tax rate.